Case Study: Status of Nutritional Assessment of Wound Healing After Appendectomy Surgery in Appendicitis Patients - Fitriani, Ade; Hamdani, Dadi; Rohimah, Risa Lutfiatul (Jurnal Vocational Nursing Sciences (VNUS), 2024)
Objective: This case study is intended to intervene and implement the nutritional status of appendicitis patients in improving the wound healing process with nausea after appendicectomy surgery. Method: In the nursing care research process, methods were used which included assessment, nursing diagnoses, planning, implementation and evaluation which were carried out for 3 days in the Anggrek BLUD room at the Banjar City Hospital. Enforcement of nursing diagnoses refers to the Indonesian Nursing Diagnosis Standards (IDHS). Indonesian Nursing Intervention Standards (SIKI), Indonesian Nursing Outcome Standards (SLKI), and nursing evaluations are documented using the SOAPIER method. Result: Nursing diagnosis of Deficit Nutrition related to postoperative nausea, nutritional status assessment for 3 days was carried out on the healing of surgical wounds. From the results of the data analysis, the researcher concluded that the nursing problems experienced by clients were nutritional deficits (D.0019) associated with postoperative nausea. The problem of excessive nutritional deficits for clients is partially resolved, marked by the loss of feelings of nausea when given food, being able to digest food properly, measuring the client's body mass index which is found to be normal, improving the client's nutrition is fulfilled by consuming high-calorie, high-protein foods. Conclusion: Conclusions can be drawn in the results of the nursing procedure commencing with evaluation, identification of nursing issues, actions, execution, and assessment of nursing. Concluded the problem of nutritional deficits related to postoperative nausea with an appendectomy with an assessment of nutritional status can improve the wound healing process as indicated by the response of clients who obtain changes in nutritional status with the wound healing process. Assessment of nutritional status is proven to be able to improve the postoperative wound healing process, the benefits of assessing nutritional status by fulfilling the client's nutrition are maximally implemented if done periodically and in stages.